Transitional Justice Accountability and Memorialisation: The Yemeni Children Affair and the Indian Residential Schools. Issue 1 (11th February 2014) - Amir, Ruth
Abstract : This article outlines the building blocks of transitional justice in democracies. Grounded in the premises of Historical Institutionalism, the article analyses the institutions and processes established and their effect on the outcomes. It offers a comparative analysis of two cases of transitional justice processes in democracies. These are the investigations of the disappearance of Yemeni children in Israel and the Indian Residential Schools Settlement in Canada. There are important similarities and differences between the two cases. In both settler societies the transgressions were part of aggressive assimilation policies directed at children in an attempt to wipe out the particular cultural influences of the children's family and community. In both cases, children were isolated from the influences of their ethnic group in order to be resocialised into the dominant culture. The dire consequences of both these were suppressed, denied and forgotten in official narratives. The different outcomes of these processes are explained by the differences in the intent to redress, the types of institution and the processes implemented.